THE RAPIDLY CHANGING ENERGYSECTOR OF INDIA (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper examines the rapidly changing energy sector in India, focusing on the strategies and adaptations of three major players: Reliance Industries, Tata Power, and Adani Power. It analyzes their pre-pandemic renewable energy investment strategies, financial approaches, and working capital management. The paper then delves into the impact of COVID-19 and the Ukraine-Russia war on these companies, highlighting their resilience and vulnerabilities. Finally, it concludes by emphasizing the need for adaptation, innovation, and a focus on clean energy as key drivers for success in the future Indian energy landscape.